Building time comparison between conventional and industrialized building system using schedule simulation - Mohammad Mahdi Tahmasebi, 1986-; Salihuddin Radin Sumadi, supervisor; Fakulti Kejuruteraan Awam (2012)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2012